Structural characterization of sugarcane lignins extracted from different protic ionic liquid pretreatments. (December 2020) - Pin, Thaynara C.; Nascimento, Viviane M.; Costa, Aline C.; Pu, Yunqiao; Ragauskas, Arthur J.; Rabelo, Sarita C.
Abstract: Previous studies based on protic ionic liquids have shown them to be effective for extracting lignins from biomass. Moreover, ILs synthesized with amine cations can promote the insertion of nitrogen into lignin, favoring its valorization for industrial applications. In this study, lignins extracted from sugarcane bagasse by eight different PILs were analyzed. Several techniques of characterization were employed (2D HSQC NMR, 31P NMR, GPC, Py-GC/MS, TGA, FTIR, and elemental analysis), seeking a deeper understanding of lignin structure post-PILS treatment. In particular, lignin obtained with acetate and lactate anions with monoethanolamonium cations showed similar structural compositions. Lignins obtained from ethylenediamonium cation combined anions acetate and lactate exhibited relatively higher molecular weights compared to the other lignins studied. The elemental analysis of these lignins further revealed the presence of nitrogen in their structures, suggesting that amination occurred. In this work we used PILs not yet reported in the literature for this purpose, and consequently obtained lignins with specific structures. Overall, our results demonstrated that depending on the PILs used, lignins with distinct properties could be obtained which might be used for value-added applications. This work covered new advances in elucidation of lignin chemical structure and opened a new path for lignin valorization. Graphical abstract: Image 1 Highlights: Lignin extracted by [2He][Ac] and [2He][Lac] showed a preserved structure. Lignin extracted by [Etid][Ac] and [Etid][Lac] exhibited relatively higher molecular weight. All lignins samples revealed the presence of nitrogen in their structures. Protic ionic liquids can support lignins industrial applications for chemicals products.